Notch Signaling in Neuroendocrine Tumors - Crabtree, Judy S.; Singleton, Ciera S.; Miele, Lucio (Frontiers in Oncology, 2016)
Carcinoids and neuroendocrine tumors (NETs) are a heterogeneous group of tumors that arise from the neuroendocrine cells of the GI tract, endocrine pancreas and the respiratory system. NETs remain significantly understudied with respect to molecular mechanisms of pathogenesis, particularly the role of cell fate signaling systems like Notch. The abundance of literature on the Notch pathway is a testament to its complexity in different cellular environments. Notch receptors can function as oncogenes in some contexts, and tumor suppressors in others. The genetic heterogeneity of NETs suggests that to fully understand the roles and the potential therapeutic implications of Notch signaling in NETs, a comprehensive analysis of Notch expression patterns and potential roles across all NET subtypes is required.